Twists and Turns in Crime Fiction—Peter Lovesey’s “Youdunnit” and Max Dorra’s “Thou shalt kill” - François Gallix (Sillages Critiques)
This article in the form of an enquiry attempts to follow the track opened by the French Oulipian François Le Lionnais and taken up again by Umberto Eco, according to which the only hypothesis left by the novel of detection is when the culprit happens to be the reader. In fact, two authors have now filled in this gap: Peter Lovesey with “Youdunnit” (1989) and Max Dorra with “Vous permettez que je vous dise tue” (1999).